Investigation into experimental toxicological properties of plant protection products having a potential link to Parkinson's disease and childhood leukaemia1. (16th March 2017) - ,; Ockleford, Colin; Adriaanse, Paulien; Berny, Philippe; Brock, Theodorus; Duquesne, Sabine; Grilli, Sandro; Hernandez‐Jerez, Antonio F; Bennekou, Susanne Hougaard; Klein, Michael; Kuhl, Thomas; Laskowski, Ryszard; et al.
Abstract: In 2013, EFSA published a literature review on epidemiological studies linking exposure to pesticides and human health outcome. As a follow up, the EFSA Panel on Plant Protection Products and their residues (PPR Panel) was requested to investigate the plausible involvement of pesticide exposure as a risk factor for Parkinson's disease (PD) and childhood leukaemia (CHL). A systematic literature review on PD and CHL and mode of actions for pesticides was published by EFSA in 2016 and used as background documentation. The Panel used the Adverse Outcome Pathway (AOP) conceptual framework to define the biological plausibility in relation to epidemiological studies by means of identification of specific symptoms of the diseases as AO. The AOP combines multiple information and provides knowledge of biological pathways, highlights species differences and similarities, identifies research needs and supports regulatory decisions. In this context, the AOP approach could help in organising the available experimental knowledge to assess biological plausibility by describing the link between a molecular initiating event (MIE) and the AO through a series of biologically plausible and essential key events (KEs). As the AOP is chemically agnostic, tool chemical compounds were selected to empirically support the response and temporal concordance of the key event relationships (KERs). Three qualitative and one putative AOP were developed by the Panel using the results obtained. The Panel supports the use of the AOP framework to scientifically and transparently explore the biological plausibility of the association between pesticide exposure and human health outcomes, identify data gaps, define a tailored testing strategy and suggests an AOP's informed Integrated Approach for Testing and Assessment (IATA). Abstract : This publication is linked to the following EFSA Supporting Publications article:http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1190/full